2013
DOI: 10.3892/ijo.2013.1879
|View full text |Cite
|
Sign up to set email alerts
|

The miR-221/222 cluster, miR-10b and miR-92a are highly upregulated in metastatic minimally invasive follicular thyroid carcinoma

Abstract: Minimally invasive follicular thyroid carcinoma (MI-FTC) is characterized by limited capsular and/or vascular invasion with good long-term outcomes. However, some cases of MI-FTC show a poor prognosis because of severe distant metastasis (i.e., metastatic MI-FTC). Nonetheless, no method has been established for predicting the prognosis of MI-FTC. This study was conducted to identify novel prognostic factors for metastatic MI-FTC by the use of microRNA (miRNA). Thirty-four patients with MI-FTC were categorized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 45 publications
1
49
0
5
Order By: Relevance
“…Similar markers were proposed for minimally invasive FTCs. MiR-10b, -92a and -221/222 cluster were significantly elevated in a group of metastatic cancers, and the expression of miR-10b was proposed to be a prognostic factor for the evaluation of the metastatic potential of minimally invasive FTC with an ORZ19.8 (54). In a study by Xiong et al, the expression levels of miR-126-3p were negatively correlated with tumor size and worse clinical outcome of both FTC and PTC patients.…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…Similar markers were proposed for minimally invasive FTCs. MiR-10b, -92a and -221/222 cluster were significantly elevated in a group of metastatic cancers, and the expression of miR-10b was proposed to be a prognostic factor for the evaluation of the metastatic potential of minimally invasive FTC with an ORZ19.8 (54). In a study by Xiong et al, the expression levels of miR-126-3p were negatively correlated with tumor size and worse clinical outcome of both FTC and PTC patients.…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…MiR-10b overexpression was first associated to metastasis in breast cancer [19], and subsequently confirmed as relevant to the development of metastasis in other types of cancer, such as nasopharyngeal [28], pancreatic [29], colorectal [30], hepatocellular [31][32][33][34], and follicular thyroid carcinoma [35]. MiR-9 up-regulation was associated with lymph node metastases in non-small cell lung cancer [36], hepatocellular carcinoma [37], breast [38,39] and colorectal cancer [40].…”
Section: Introductionmentioning
confidence: 97%
“…Among these cancer-related miR, miR-92a has been demonstrated to possess an oncogenic role in different cancer types, and several targets have been identified (13)(14)(15). A previous study indicated that miR-92a promoted the metastasis of colorectal cancer cells through inhibition of phosphatase and tensin homolog, leading to the upregulation of the phosphoinositide 3-kinase/protein kinase B pathway (13).…”
Section: Introductionmentioning
confidence: 99%